E. Husserl’s Phenomenological Conception of Personality: Philosophical Foundations and Historical Fate - Pivorius., Vytautas (Problemos, 1989)
In the paper an attention is payed to the relation between E. Husserl’s conception of personality and the main theoretical statements of the modern philosophy. At the same time it is showed that in E. Husserl’s phenomenology an inclination towards the irrationalistic treatment of human subjectivity takes place. The relation between the way in which the problem of personality is put forward in the existential philosophy (Sartre, Merlau-Ponty) and E. Husserl’s phenomenology is pointed out too.